استخدام الإنشاء الحرّ لترقية مهارة الكتابة لطالبات قسم اللغات في المدرسة الثانوية الحكومية الإسلامية تامباؾ براس جومبانج - Iis Muhissoh (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2015)
Being afraid of making linguistic errors and feeling hard to express ideas made students of Madrasah Aliyah Negeri Tambakberas Jombang think that writing is difficult. Therefore, they are poor in writing. That is why this classroom action research was conducted. This research was done in three cycles. The implementation of teaching-learning activity by using free writing runs well. The students’ competence in writing in all cycles increased after using free writing technique. Therefore, there is significance relation between using free writing technique and the improvement of students skill in writing